Acts Against the Law in the Buying and Selling of Football Tickets Indonesia VS. Australia - Asyrafi, Muhammad Naufal; Iskandar, Hardian (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
Ticket sales through calo often occur in football matches in Indonesia, such as the Indonesia vs Australia match at Gelora Bung Karno. This phenomenon takes advantage of the public's high enthusiasm for football, which often causes losses to consumers. Many buyers are trapped by brokers who sell tickets at a much higher price than the official price to earn personal or group profits. It is clearly an illegal act that violates rules, norms, and laws, especially in the perspective of civil law. The existence of ticket candidates creates unfairness in the ticket sales system that should be transparent, fair, and affordable to all walks of life. Their existence indicates a loophole in the supervision and enforcement of the law that must be repaired immediately. This is important to protect consumers' rights and maintain the integrity of sporting events that all parties should be able to enjoy fairly. Normative research methods are used to analyze the regulations and responsibilities related to the use of calo services in the transaction of buying and selling tickets for Indonesian vs. Australian football matches. From the research results, it was found that the regulation regarding ticket candidates in Indonesia is still insufficient and has not provided legal certainty for consumers. In this case, the act of ticket candidates can be considered as an act against the law that harms the community. Legal efforts that can be made include filing a civil suit and asking the perpetrator to compensate for the losses incurred by consumers.